Acanthus Ornament of the Ishkhan Cathedral and Its Parallels in the Late Antique and Early Christian Art - Asryan, Arpine A. (Actual Problems of Theory and History of Art, 2015)
In the 10th–11th centuries Tayk was undergoing unprecedented period of cultural flourishing based on tradition of three cultures: Armenian, Georgian and Byzantine. From the art historical point of view monuments of Tayk are not studied enough. First of all, it regards ornamental motifs that are an inseparable part of architectural ensembles. In a certain sense this is the reason why they have never been the subject of a special study, though should be studied specially. Rich decoration of the Tayk monuments gives us enough material with the acanthus motif to be highlighted. Among the monuments of Tayk the cathedral in Ishkhan is distinguished for the diversity of its exterior decor. Decorative repertoire, along with other elements, is made up of floral ornaments with the dominance of acanthus. It is acanthus that is depicted on the most vivid and significant parts of the façade: window frames, entrance tympani, and the tholobate. Known from Classical antiquity, the acanthus motif became widespread in Early Christian art, later it was inherited by that of Byzantium and the neighboring countries, Armenia among them. In the 7th century acanthus became one of the important elements in the exterior décor. Acanthus from Ishkhan finds iconographic parallels in Late Antique and Early Christian art, particularly in pavement, in relief, and in minor architectural forms. Acanthus motif and its versatile variations presented in the exterior décor of the Ishkhan cathedral, kept developing in the church architecture of Transcaucasia.